1974
DOI: 10.1042/bj1410079
|View full text |Cite
|
Sign up to set email alerts
|

The calcium-induced dissociation of human plasma clotting Factor XIII

Abstract: 1. Large quantities of human Factor XIII were prepared from ethanol precipitates of outdated human plasma. 2. Material homogeneous after chromatography on DEAE-cellulose was further resolved into two proteins, A and B, after filtration on Sepharose 6B. 3. Protein A has a molecular weight of 350000 and a subunit structure a(2)b(2) and is activated by thrombin and calcium. Protein B is inactive and probably has a subunit structure b(2). 4. Calcium causes protein A, after thrombin cleavage, to fragment to give pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
32
0

Year Published

1975
1975
1999
1999

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 17 publications
1
32
0
Order By: Relevance
“…By measurement of the incorporation of iodo[14C]acetic acid, Chung et al (17) concluded that all of the free -SH groups of plasma FXIII are in the a chains and that each a chain has six -SH groups and no disulfide bonds. Others showed that there is a single reactive cysteine per a chain (3,12,20 (3,5,10,12).…”
Section: Comparison Of the Protein Seqdence With The Amino Acidmentioning
confidence: 99%
See 1 more Smart Citation
“…By measurement of the incorporation of iodo[14C]acetic acid, Chung et al (17) concluded that all of the free -SH groups of plasma FXIII are in the a chains and that each a chain has six -SH groups and no disulfide bonds. Others showed that there is a single reactive cysteine per a chain (3,12,20 (3,5,10,12).…”
Section: Comparison Of the Protein Seqdence With The Amino Acidmentioning
confidence: 99%
“…On the basis of our studies and earlier data, we propose a molecular model for FXIIIa that shows the sites of activation and inactivation by thrombin and the location of the reactive thiol center and of a putative Ca2+-binding domain. (12), in which a TSK G4000SW column (7.5 mm i.d. x 60 cm, 8020 Biochemistry: Takahashi et al…”
mentioning
confidence: 99%
“…In the blood, activation of circulating fXIII requires thrombin cleavage, calcium ions (1.5 mM) (12)(13)(14), and fibrin(ogen) (15). High levels of calcium (Ͼ50 mM) can activate fXIII without the use of thrombin (15), and it has recently been shown that platelet fXIII can be activated nonproteolytically in vivo (16).…”
mentioning
confidence: 99%
“…As such, these inhibitors should be classified as Type I within the context of inhibitors giving rise to hemorrhagic disorders of fibrin stabilization (2). Conversion of the plasma zymogen to the active transamidase is known to occur in two distinct steps (21)(22)(23)(24). The first is catalyzed by thrombin and the second depends rather specifically upon the presence of Ca21 ions.…”
Section: Resultsmentioning
confidence: 99%
“…The first is catalyzed by thrombin and the second depends rather specifically upon the presence of Ca21 ions. Modification of the ab ensemble in the zymogen by thrombin affects only a and, while converting this subunit to a somewhat smaller a' component (25,26), it allows the two different subunits to remain associated within an a'b protomer (21)(22)(23)(24). Furthermore, the hydrolytically altered species still has no measureable transamidase activity (21,22 and while IgG Warsaw produced a complete inhibition (as long as it was applied bef'ore adding Ca2+; vertical broken line), remarkably IgG San Juan had no effect whatsoever on the platelet factor (Fig.…”
Section: Resultsmentioning
confidence: 99%